The nature of inclined seismic boundary in the Earth crust of the Scythian plate along the DOBRE-5 Profile - L. Farfuliak (Геофизический журнал, 2015)
Geological and tectonic interpretation of high-speed seismic model along the profile DOBRE-5 elaborated in 2011 by DSS method (wide-angle refraction and reflection (WARR)) with the main aim of clarifying the structure of the lithosphere and geodynamic features of the southwestern edge of the East-European platform (Scythian plate) has been conducted. Amplifying volumetric seismic tectonic model of the Scythian plate has been plotted; structural-high-speed element — sloping seismic boundary along the DOBRE-5 profile has been revealed, its location has been defined more precisely and possible mechanisms of formation have been proposed: it corresponds to the northern border of the Early Permian active over-thrust or thrust edge of southern dip and of formation of front-rank molassa sag, the so-called Euxinian orogenic belt or the North Crimean suture formed by the closure of the Paleo-Tethys Ocean in the late Paleozoic—Triassic, subduction of the East-European platform (EEP) under the Scythian plate (SP) southward and their collision. On the surface Pre-Cretaceuos basement of the North Crimean suture can be traced as Golitsyn and Azov fault zones usually considered as the border between EEP and SP. Dipping seismic border is a listric surface that falls to the south-southeast, with angles in the longitudinal intersection, α = 17°, and in sections perpendicular to the EEP and SP, α = 22°to 38°. This inclination of the DSB is close to the dip of the South-Crimean suture zone that was previously assumed by Yudin V.V.